Pemanfaatan Limbah Organik Pasar untuk Produksi Pupuk Organik Cair sebagai Alternatif Pengelolaan Sampah Berkelanjutan - Wahyudin, Wahyudin; Fatmalia, Enida (Universitas Muhammadiyah Kendari, 2026)
The increasing generation of organic waste from traditional markets remains a major challenge in sustainable urban waste management. This study aimed to evaluate the quality of liquid organic fertilizer (LOF) produced from organic waste collected from Karang Jasi Traditional Market using Effective Microorganisms 4 (EM4) as a biological fermentation agent for circular economy-based waste management. A descriptive-comparative experimental method was employed using EM4 concentrations of 0% (P0), 5% (P1), 10% (P2), and 15% (P3). The fermentation process was conducted for 14 days, and the resulting liquid organic fertilizer was evaluated based on physical, chemical, microbiological, and heavy metal parameters according to the Indonesian Ministry of Agriculture Regulation No. 261/KPTS/SR.310/M/4/2019. The results indicated that variations in EM4 concentration affected the quality of the liquid organic fertilizer, particularly in total nitrogen, C/N ratio, and fermentation stability. The 10% EM4 concentration represented the optimum fermentation condition, resulting in more stable fertilizer characteristics compared to the other treatments. Parameters including pH, Pb content, total nitrogen, and C/N ratio met or approached the required quality standards, whereas C-organic content, Fe, and Escherichia coli still require further optimization to comply with national quality standards. This study contributes to the development of liquid organic fertilizer production from traditional market organic waste through a comprehensive quality evaluation based on national standards. These findings highlight the potential utilization of traditional market organic waste as a sustainable and value-added source-based waste management strategy to support circular economy implementation in urban areas.